Spatial memory deficit across aging: current insights of the role of 5-HT7 receptors - Beaudet, Gregory; Bouet, Valentine; Jozet-Alves, Christelle; Schumann-Bard, Pascale; Dauphin, François; Paizanis, Eleni; Boulouard, Michel; Freret, Thomas (Frontiers in Behavioral Neuroscience, 2015)
Elderly persons often face biological, psychological or social changes over time that may cause discomfort or morbidity. While some cognitive domains remain stable over time, others undergo a decline. Spatial navigation is a complex cognitive function essential for independence, safety and quality of life. While egocentric (body-centered) navigation is quite preserved during aging, allocentric (externally-centered) navigation — based on a cognitive map using distant landmarks — declines with age. Recent preclinical studies showed that serotonergic 5-HT7 receptors are localized in brain regions associated with allocentric spatial navigation processing. Behavioral assessments with pharmacological or genetic tools have confirmed the role of 5-HT7 receptors in allocentric navigation. Moreover, few data suggested a selective age-related decrease in the expression of 5-HT7 receptors in pivotal brain structures implicated in allocentric navigation such as the hippocampal CA3 region. We aim to provide a short overview of the potential role of 5-HT7 receptors in spatial navigation, and to argue for their interests as therapeutic targets against age-related cognitive decline.